Safety and kinetic parameters analysis for 1, 1, -Di(tert-butylperoxy) cyclohexane mixed with monoammonium phosphate. (March 2015) - Su, C.H.; Huang, S.T.; Lin, C.P.; Tseng, J.M.; Mannan, M. Sam
Abstract: Runaway reactions by organic peroxides have occurred throughout the world. In this study, we used 1, 1, -Di(tert-butylperoxy) cyclohexane (CH) 70 mass% as the main material, which was extensively employed as initiator for styrene in polymerization. Fire extinguishers are the first fire-fighting apparatus when fires occur. If a fire extinguisher has sat idle for a long time, which would cause the extinguishing agent to damp, it cannot achieve the desired effect and be properly handled at the start of the accident, thereby causing more casualties and property losses. CH 70 mass% was employed to mixed with monoammonium phosphate (MAP) for understanding the phenomenon by applying differential scanning calorimetry (DSC). Safety parameters also were carried out for more deeply understanding the basic characteristics for preventing an accident from occurring, in terms of applying CH 70 mass% as the initiator in the manufacturing process. Highlights: CH 70 mass% was mixed with monoammonium phosphate (MAP). Differential scanning calorimetry (DSC) was employed to test the affection of MAP with CH 70 mass%. Moisture can affect the efficiency to put out a fire.